Centesimal composition and sugar content of green pepper flour - Nascimento, Ana Marinho do; Costa, Franciscleudo Bezerra da; Silva, Jéssica Leite da; Santos, Kalinne Passos dos; Gadelha, Tatiana Marinho (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
The capsicum annuum L., is a vegetable of extreme economic importance in Brazil. Information on the nutritional composition of foods is a parameter that assists consumers during the choice of products. The objective of this work was to evaluate the centesimal composition and the sugar content of fresh and dry green peppers at 60 oC in order to identify if these components remained after drying. The experiment was conducted in a completely randomized design with 2 treatments and 5 replicates. Green peppers from CEASA of the city of Patos-PB were used. The peppers were packed in plastic boxes and transported to the laboratory where they were selected, washed, sanitized, processed and dried in a greenhouse with circulation and air renewal at 60 ºC. At the end of the drying the crushing and sieving were carried out to carry out the analyzes of moisture, ashes, lipids, proteins and total and reducing sugars. The carbohydrate contents were calculated by the difference between 100 and the sum of the percentages of humidity, protein, lipids and ashes. The energy value was calculated by multiplying these values by the atwater factors. The components showed a significant difference in the treatments studied, it was observed that there was an increase of macronutrients after drying. The centesimal composition of pepper flour was concentrated after drying, indicating that the applied method is an alternative to take advantage of the large productions in the harvest period.